REACTIVE OXYGEN SPECIES (RO S) , TOTAL ANTIOXIDANT CAPACITY (AO C) AND MALONDIALDEHYDE (M DA) MAKE A TRIANGLE IN EVALUATION OF ZINC STRESS EXTENSION - M. M. Tirani; M. M. Haghjou th (Journal of Animal and Plant Sciences, 2019)
Reactive oxygen species (ROS) are generated in response to the various environmental stresses, and overproduction of ROS can lead to the lipid peroxidation, which often is monitored by measuring the malondialdehyde (MDA). Nevertheless, the extent of oxidative stress is partly dependent on the total antioxidant capacity (AOC) of plant cells. In many experiments, the assessment of oxidative stress is based on the measurement of ROS only or more commonly individual antioxidants, but a more reliable assessment of oxidative stress requires the simultaneous measurement of ROS, AOC and MDA levels. In this study, the effects of different ZnO concentrations were studied on the oxidant and antioxidant potentials, and also on MDA levels in tobacco plants. Moreover, the significant correlations were considered between the indices, which were evaluated via different methods. Results showed that both Zn deficiency and excess levels led to the increased ROS/H2O2 production, Chl a/b reduction, electrolytes leakage and lipid peroxidation, compared to the control. The inverse conditions were observed for the adequate ZnO amount (1μM) with the highest AOC level. ROS was significantly correlated with H2O2 (P<0.01, R= 0.8) and MDA (P<0.01, R= 0.6-0.8) but not with AOC. Only MDA-PhB method caused a significant correlation (P<0.01, R= -0.7) with the results from AOC methods. Unlike Chla/Chlb, the electrolyte leakage was often significantly correlated with other stress indices. In general, a dependency to the used method was observed for finding the significant correlations among oxidative stress markers, and their simultaneous measurements were also suggested for the better interpretation of data.
Keywords: Antioxidant Capacity; Malondialdehyde; Reactive Oxygen Species; Zinc Stress